Analysis of Contractor's Construction Claim Submission - Lilis Novitasari; Micky Fetriani; Monika Natalia (Universitas Negeri Padang, 2025)
Construction projects are basically bound by a contract document. The document regulates the duration of the project, the scope of the project and the specifications of the project as well as the rights and obligations of each party between the contractor and the owner. With this contract, it is expected that the construction project can run smoothly and on time. However, claims are still often submitted in the construction process. Therefore, a study was conducted to determine the factors causing claims made by the contractor to the owner. Using a quantitative descriptive approach method, the results showed that the factors that dominate the submission of contractor claims are the owner's delay in approving shop drawings with an Importance Index of 0.871. There were design changes made by the owner with an Importance Index of 0.842. The occurrence of high rainfall intensity with an Importance Index of 0.751. The requested material is not available in the city but must be indented with an Importance Index of 0.743. There is additional work outside the contract specified by the Importance Index of 0.729.